Identification of measles virus-specific hemolysis-inihibiting antibodies separate from hemagglutination-inhibiting antibodies. - Norrby, E (1975)
The occurrence of antibodies giving hemolysis inhibition (HLI) but not hemagglutination inhibition (HI) was examined in human convalescent and rabbit hyperimmune sera. HI antibodies, which through their interaction with hemagglutinin components display HLI activity, were removed by absorption with Tween 80-ether (TE)-treated measles virus material. This absorption did not change the titer of non-HI HLI antibodies. After removal of HI antibodies from 16 late measles convalescent sera and three batches of gamma globulin. HLI antibody titers showed a two- to eightfold reduction. The titers of neutralizing antibodies were reduced from 1/4 to 1/20 of the original titers. There was a good correlation between the titers of neutralizing and HLI antibodies both in sera from which HI antibodies had been removed by absorption and in sera spontaneously showing markedly higher HLI than HI antibody titers. HLI antibodies with these characteristics could be identified in HI tests when whole virus instead of TE-treated material was used an antigen and anti-antiserum was added to the tests. In contrast to the situation in human sera, antibodies remaining after removal of HI antibodies from rabbit hyperimmune sera against purified virus particles were detectable in neutralization and HLI tests only in the presence of anti-antiserum. However, virus particles from which the major fraction of all envelope projections had been removed by treatment with 0.004% trypsin induced the production of non-HI HLI antibodies active also in the absence of anti-antiserum. TE and formalin treatment destroyed the hemolytic activity of virus preparations and also their capacity to induce a production of non-HI HLI antibodies.